Adaptive prediction of stock exchange indices by state space wavelet networks - Brdyś, Mietek A.; Borowa, Adam; Idźkowiak, Piotr; Brdyś, Marcin T. (Zielona Góra: Uniwersytet Zielonogórski)
The paper considers the forecasting of the Warsaw Stock Exchange price index WIG20 by applying a state space wavelet network model of the index price. The approach can be applied to the development of tools for predicting changes of other economic indicators, especially stock exchange indices.
Keywords: forecasting; stock exchange; artificial intelligence; state space wavelet network; simulated annealing